Liquid Slosh Suppression By Using Hybrid Model-Free Fuzzy-PID Controller With Derivative Filter - Mohd Tumari, Mohd Zaidi; Abd Rashid, Wan Norhisyam; Ab Hadi, Nik Azran; Ahmad, Mohd Ashraf; Suid, Mohd Helmi; Ghazali, Mohd Riduwan (JARDCS, 2018)
This study presents a control scheme for liquid slosh control by using hybrid Fuzzy proportional-integral-derivative (fuzzy-PID) controller with derivative filter (Fuzzy-PIDF). Model-based control approaches are difficult to apply in practice. Thus, hybrid model-free Fuzzy-PIDF is more attractive to implement for liquid slosh control. The relevant advantage of this proposed controller is its simple to design without the knowledge of liquid slosh model. Two inputs of fuzzy inference system which are system error and derivative error are scaled by two coefficients, Kin1 and Kin2 respectively. Five triangular membership functions are defined for both inputs while nine triangular membership functions are defined for the output. Then, the fuzzy output is connected to PIDF in order to suppress the liquid slosh. With the purpose to confirm the design of control scheme, a liquid slosh model is considered to represent the lateral slosh motion. Supremacy of the proposed control scheme is shown by comparing the results with fuzzy-PID without derivative filter. Finally, it is seen from the simulation results that the proposed control scheme has able to reduce the liquid slosh without unambiguously model the liquid slosh behavior.